Breed, age, and environmental effects on bull semen in the low tropics - Sánchez Viafara, Jesús Alfonso; Vergel Martínez, Greysy Dariana; Vergel Martínez, Breysy Yuliana; Valencia Giraldo, Julián Alonso (Spei Domus, 2024)
Objective. This study aimed to identify factors that affected the semen quality of breeding bulls in the low tropics of Colombia. Materials and methods. The rest period, breed (B), and environmental (E) effects on sperm concentration and semen volume were examined in a first analysis with 399 bulls. Subsequently, breed and environmental effects on sperm concentration, semen volume, and progressive motility, in addition to breed (breed or crossbreed) effects on scrotal circumference, were examined in a second analysis performed with 1848 bulls. Results. The scrotal circumference of Jersey×Gyr bulls was significantly (p
Keywords: animal reproduction; bulls; testicles; semen